The Association of TLR2, TLR3, and TLR9 Gene Polymorphisms With Susceptibility to Talaromycosis Among Han Chinese AIDS Patients in Guangdong - Wang, Min; Li, Linghua; Xiao, Saiyin; Chen, Wanshan; Hu, Fengyu; Li, Feng; Guo, Pengle; Chen, Xiejie; Cai, Weiping; Tang, Xiaoping (Frontiers in Cellular and Infection Microbiology, 2021)
Background Talaromycosis (TM) caused by Talaromyces marneffei (T. marneffei) is a growing public health concern. Although Toll-like receptor (TLR) genes play a critical role in the host defense against fungal infection, the influence of polymorphisms in these genes on the susceptibility of acquired immune deficiency syndrome (AIDS) patients to TM remains unknown. This study aims to uncover the associations of single nucleotide polymorphisms (SNPs) in TLR genes with TM susceptibility among patients with AIDS. Methods Altogether 200 AIDS patients complicated with TM, 200 matched AIDS patients without TM, and 76 healthy controls (HCs) were enrolled in this case-control study. In total, 23 SNPs in the TLR2, TLR4, and TLR9 genes, which may influence the susceptibility of AIDS patients to TM, were checked by the time of flight mass spectrometry (TOF/MS) method among these Han Chinese subjects. Results No significant differences in genotype or allele frequencies of selected SNPs were found among the TM group, Non-TM group, and HC group. Haplotype analysis also demonstrated no correlation of these SNPs with TM. However, subgroup analysis showed that the genotype TT and the T allele in TLR2 SNP rs1339 were more frequent in typical TM cases than controls (50.0 vs. 35.8%, 70.5 vs. 59.7%); the frequency of the GT genotype in TLR2 SNP rs7656411 was markedly higher in severe TM cases compared to controls (57.8 vs. 34.4%). Conclusion Our results demonstrate a genetic connection of TLR2 SNPs rs1339 and rs7656411 with an increased susceptibility and severity of TM among Han Chinese populations.